Prevalence of premature birth in conditions of global warming - V.I. Tsymbaliuk; S.N. Vadziuk; T.I. Tolokova; P.S. Tabas (Medičnì Perspektivi, 2021)
The dynamics and likely associative link between global warming and the prevalence of preterm births in Ukraine over the years 2009-2018 was studied. to form modern ideas about the prognosis and prevention of this pathology. Data on medical care for pregnant women, mothers and parturients and adverse effects of pregnancy on preterm birth (form 21) for the period 2009-2018 were obtained from the municipal non-profit enterprise "Ternopil Regional Center of Public Health of Ternopil Regional Council". The correlation between the number of premature births per 100 births according to the average annual air temperature according to the Global Historical Climatology Network from the US Department of Ocean and Atmospheric Research in the climatically homogeneous regions of Ukraine was estimated. Predictive analysis of time series was performed by the method of integrated auto-regression of the moving average (ARIMA). The model error was estimated by calculating the absolute percentage error of the mean (MAPE). Statistical processing of materials was performed using programs Statistica 6.0 (StatSoft, USA) and open statistical package "R". The study meets modern requirements of moral and ethical standards regarding the provisions of legislative acts of Ukraine.  Analysis of these reports of women's counseling shows an increase in the average number of preterm births from 2.88 per 100 births in the total number of births in Ukraine – 491445 in 2009 to 3.33, per 100 births in the total number of 309191 in 2018, which testifies to  a significant increase in premature births in our country. Since 2009, there has been an annual, varying degree of increase in average annual air temperature in Ukraine. As a result of the correlation analysis, a significant strong direct correlation was established between the average level of premature birth and the average annual air temperature in Ukraine (r=0.84, p<0.05). Regression analysis revealed a significant increase in the number of premature births (per 100 births) in 1, 2, 5, 6, 7, 8 and 10 climatically homogeneous regions and a tendency to increase in, respectively, 3, 4, 9, 11 and 12 climatically homogeneous regions of Ukraine.  Based on the analysis of data on the average annual air temperature in Ukraine for 2009-2018, the average annual air temperature in Ukraine is projected to increase by 0.3 ° С in 3 years (MAPE <10%, p<0.05). The annual number of premature births is expected to increase (cases per 100 births) in 3 years by 0.4 cases per 100 births (MAPE <10%, p <0.05). In the context of global warming, the number of negative consequences of pregnancy is increasing, namely idiopathic premature termination of pregnancy with the birth of premature infants. Strong correlations have been established between the annual number of premature births and the average annual air temperature in Ukraine. Regression models of preterm birth showed a significant increase in 1, 2, 5, 6, 7, 8, and 10 climatically homogeneous regions and a tendency to increase in 3, 4, 9, 11 and 12 climatically homogeneous regions. The annual number of premature births in Ukraine is projected to increase by 2023 by 20 cases per 100 births compared to 2018. The strategy for preventing premature births and related adverse effects of pregnancy should include the identification of global warming as a risk factor for increasing level of this pathology.